Laryngeal myxedema as a cause of reversible subglottic stenosis in a newborn. (November 2022) - Levi, Eric; Nisa, Lluís
Abstract: Myxedema is a manifestation of severe hypothyroidism, and when affecting the larynx it constitutes a rare cause of upper airway obstruction. We present a case of laryngeal myxedema in a newborn causing subglottic stenosis. The atypical aspect of the stenosis along with a thyroid goiter and a positive screening for neonatal hypothyroidism allowed the diagnosis of laryngeal myxedema. Thyroid hormone replacement and non-invasive ventilation led to quick resolution while avoiding invasive approaches. Laryngeal myxedema is possibly underdiagnosed. Physician awareness is essential to avoid pitfalls in such children with reversible airway obstruction. Highlights: Laryngeal myxedema is a rare cause of reversible upper airway stenosis A soft, non-circular aspect of the stenosis along with a goiter and/or congenital hypothyroidism seem to be the typical feature of laryngeal myxedema Early diagnosis, thyroid replacement therapy and non-invasive respiratory support are key to avoid invasive airway procedures